2021
DOI: 10.1111/nph.17717
|View full text |Cite
|
Sign up to set email alerts
|

mTERF18 and ATAD3 are required for mitochondrial nucleoid structure and their disruption confers heat tolerance in Arabidopsis thaliana

Abstract: Summary Mitochondria play critical roles in generating ATP through oxidative phosphorylation (OXPHOS) and produce both damaging and signaling reactive oxygen species (ROS). They have reduced genomes that encode essential subunits of the OXPHOS machinery. Mitochondrial Transcription tERmination Factor‐related (mTERF) proteins are involved in organelle gene expression, interacting with organellar DNA or RNA. We previously found that mutations in Arabidopsis thaliana mTERF18/SHOT1 enable plants to better tolera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…On the other hand, mitochondria looked enlarged in size and less electron dense than those from WT, suggesting that it is the mitochondrion that is predominantly affected in radA . Bigger mitochondria were also reported in other mutants impaired in mitochondrial gene expression or genome maintenance, such RNAi lines affected in the expression of organellar RNase P and in mutants of SHOT1 that is apparently involved in the organization of mitochondrial nucleoids [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, mitochondria looked enlarged in size and less electron dense than those from WT, suggesting that it is the mitochondrion that is predominantly affected in radA . Bigger mitochondria were also reported in other mutants impaired in mitochondrial gene expression or genome maintenance, such RNAi lines affected in the expression of organellar RNase P and in mutants of SHOT1 that is apparently involved in the organization of mitochondrial nucleoids [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies based on the phenotype of mTERF mutants suggested that these genes are essential for functional acclimation to diverse abiotic stresses, including heat stress [ 94 ]. For instance, it has been shown that an insertional mutant of mTERF18 is more heat-tolerant than the wild-type plants and exhibited higher transcript levels of HSPs in Arabidopsis [ 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to multiple intragenic suppressors (Lee et al, 2005), we also identified extragenic suppressors. We previously reported identification of the extragenic suppressor shot1 (suppressor of hot1-4 1), which is a bypass suppressor mutant with defects in mitochondrial function (30,31). Here, we report the isolation of three additional extragenic suppressor mutants (shot2, 3 and 4) and the identification of the shot2 mutation in a gene encoding the CstF77 protein (AT1G17760), a component of the polyadenylation complex involved in formation of the 3' end of mRNA.…”
Section: Introductionmentioning
confidence: 88%
“…The first mutant allele of CstF77 identified in A. thaliana, cstf77-1, carries a deletion from Y339 to K385 in the HAT-C domain, and was reported as one of the suppressors of overexpressed FLOWERING CONTROL LOCUS A (FCA) (34). A T-DNA insertional knockout allele, cstf77-2, was initially reported to be lethal in the same study (31), but later found to be viable, although it has serious growth defects (43). Importantly, the shot2 mutation has no negative effect on plant growth under standard growth conditions, indicating that the shot2 mutation does not cause any obvious defects to CstF77 function in the absence of temperature stress (Additional file 1: Fig.…”
Section: The Shot2 Gene Encodes Cstf77 a Component Of The Pre-mrna 3′ End Processing Complexmentioning
confidence: 99%